2019
DOI: 10.5897/ajps2019.1776
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomic significance of the vegetative anatomy of members of genera Colocasia (L.) Schott and Xanthosoma (L.) Schott in the family Araceae

Abstract: Anatomical attributes are important for taxonomic studies of plants. This study investigated foliar and petiole anatomy of some members of the genera Colocasia and Xanthosoma. Similar and diagnostic characters critical for the taxonomy of the two genera were identified. The similar characters include, polygonal epidermal cell shape, straight adaxial anticlinal wall pattern, brachyparacytic stomata type, elliptic shaped stomata and unmodified raphide type. The presence of papillae on the adaxial surfaces of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Shreds of evidence from anatomical studies have been used for the delimitation of taxa as reported by Metcalfe and Chalk (1979); Aguoru and Okoli (2008), Arogundade and Adedeji (2019). Carlquist in 1961 had earlier submitted that wood anatomical characters are of taxonomic and phylogenetic importance, while more recently, Liu et al (2020) noted that anatomical properties of wood relate closely to several factors amongst which is their genetic origin.…”
Section: Discussionmentioning
confidence: 99%
“…Shreds of evidence from anatomical studies have been used for the delimitation of taxa as reported by Metcalfe and Chalk (1979); Aguoru and Okoli (2008), Arogundade and Adedeji (2019). Carlquist in 1961 had earlier submitted that wood anatomical characters are of taxonomic and phylogenetic importance, while more recently, Liu et al (2020) noted that anatomical properties of wood relate closely to several factors amongst which is their genetic origin.…”
Section: Discussionmentioning
confidence: 99%